Abnormally low heat flow in Southeast China resulted from remnant slab subducted beneath the east Asian lithosphere. (27th April 2022) - Gan, Haonan; Wang, Guiling; Wang, Bo; Wang, Xiao; Lin, Wenjing; Yue, Gaofan; Tan, Xianfeng
Abstract: Subducted remnant slabs play an important role in the geodynamics and evolution of the Earth, but their behaviour in the mantle is not well understood. Terrestrial heat flow and thermal lithosphere structure provide crucial constraints on lithospheric dynamics. Based on whole‐well steady‐state temperature logs and conductivity measurements of core samples from a scientific borehole, we obtained a new high‐quality terrestrial heat flow values for East Asia. The heat flow was calculated at 60.6 ± 16.0 mW/m 2 with a high crust/mantle heat flow ratio of 1.41, suggesting a hot‐crust‐cold‐mantle lithospheric structure. The thermal lithospheric thickness of eastern Fujian is estimated to be 152–166 km, indicating a thick and cold lithosphere. We demonstrate that the cooling of the lithosphere is caused by a remnant palaeo‐slab of the Palaeo‐Pacific plate subducted beneath SE China. The remnant slab blocked heat convection into the bottom of the lithosphere of the Eurasian Plate.